Implementation of Mother Toddler Classes in Improving Mothers' Attitudes about Toddler Health through Interprofessional Education at Leuwigajah Public Health Center Area - Ryka Juaeriah; Dyeri Susanti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Maternal and Child Health (MCH) is one of Indonesia’s main priorities for health development. Toddlers are one of the populations most at risk of various health problems. Monitoring growth and development and prevention of disease in toddlers is essential to improve the health of toddlers. Using MCH Handbook is one of the strategies for community empowerment, especially for families, to maintain and obtain quality health services. Health services in Indonesia are currently still carried out by a single profession, quality health services can be achieved through collaborative practice. A program for developing an attitude of interprofessional collaboration in the practice of health services is needed. The provision on collaboration can apply from the educational stage through Interprofessional Education (IPE). This community service aims to determine the improvement of mothers' attitudes about the health of children under five after the implementation of IPE at the Integrated Healthcare Center Leuwigajah public health center area (RW 04, 11,13 and 15). This community service was carried out for 4 weeks involving as many as 50 mothers with toddlers, each class consisted of 10 mothers accompanied by facilitators, cadres, midwifery students, and nursing. In the first week before the class started, questionnaires were distributed to the mothers, and in the last week (4th) a questionnaire containing the mothers’ attitudes distributed again. The distribution of counseling materials every week is adjusted to the competence of each accompanied profession by a facilitator. The results of this community service found that before being given counseling materials to the class of mothers under five, most of the mother's knowledge was in the category sufficient (74%), and after being given counseling materials, mother's knowledge increased to a good category (70%). This community service concludes that applying IPE to the class of mothers of children under five can change the attitude of mothers about the health of children under five.